Coordinated interplay between palmitoylation, phosphorylation and SUMOylation regulates kainate receptor surface expression - Yucel, Busra P.; Al Momany, Enaam M.; Evans, Ashley J.; Seager, Richard; Wilkinson, Kevin A.; Henley, Jeremy M. (Frontiers in Molecular Neuroscience, 2023)
Kainate receptors (KARs) are key regulators of neuronal excitability and synaptic transmission. KAR surface expression is tightly controlled in part by post-translational modifications (PTMs) of the GluK2 subunit. We have shown previously that agonist activation of GluK2-containing KARs leads to phosphorylation of GluK2 at S868, which promotes subsequent SUMOylation at K886 and receptor endocytosis. Furthermore, GluK2 has been shown to be palmitoylated. However, how the interplay between palmitoylation, phosphorylation and SUMOylation orchestrate KAR trafficking remains unclear. Here, we used a library of site-specific GluK2 mutants to investigate the interrelationship between GluK2PTMs, and their impact on KAR surface expression. We show that GluK2 is basally palmitoylated and that this is decreased by kainate (KA) stimulation. Moreover, a nonpalmitoylatable GluK2 mutant (C858/C871A) shows enhanced S868 phosphorylation and K886 SUMOylation under basal conditions and is insensitive to KA-induced internalisation.These results indicate that GluK2 palmitoylation contributes to stabilising KAR surface expression and that dynamic depalmitoylation promotes downstream phosphorylation and SUMOylation to mediate activity-dependent KAR endocytosis.